Encapsulated graphene‐based Hall sensors on foil with increased sensitivity. Issue 12 (6th June 2016) - Wang, Zhenxing; Banszerus, Luca; Otto, Martin; Watanabe, Kenji; Taniguchi, Takashi; Stampfer, Christoph; Neumaier, Daniel
Abstract : The encapsulation of graphene‐based Hall sensors on foil is shown to be an effective method for improving the performance in terms of higher sensitivity for magnetic field detection. Two types of encapsulation were investigated: a simple encapsulation of graphene with polymethyl methacrylate (PMMA) as a proof of concept and an encapsulation with mechanically exfoliated hexagonal boron nitride (hBN). The Hall sensor with PMMA encapsulation already shows higher sensitivity compared to the one without encapsulation. However, the Hall sensor with graphene encapsulated between two stacks of hBN shows a current and a voltage normalized sensitivity of up to 2270 V/AT and 0.68 V/VT, respectively, which are the highest reported sensitivity values for Hall sensors on foil so far.